Development of Teaching Materials Based on Melayu Culture IPAS Learning in Elementary Schools - Guslinda; Munjiatun; Kartika Sari, Intan; Alifarani, Afra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This research aims to develop a Melayu culture-based teaching material product for IPAS learning in elementary schools. This research uses the Research and Development (R&D) method with a 4D development model, this research is limited to the Development stage. At the Define stage, an analysis of the material presented in teaching materials is carried out which is adapted to students. In the Design stage, the selection of media is carried out in accordance with the objectives. With the analysis carried out, the selected media that will be developed are teaching materials related to Melayu Riau culture and the teaching materials developed will be in the form of textbooks. The Development stage was validated with material, media and language experts. The assessment by material experts shows an average of 3.81 with a percentage of 95.17% getting the